2011
DOI: 10.1007/s10067-011-1810-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-center, retrospective analysis of efficacy and safety of tacrolimus as a second-line DMARD in combination therapy and the risk factors contributing to adverse events in 115 patients with rheumatoid arthritis

Abstract: To retrospectively evaluate the efficacy and safety of combination therapy with tacrolimus (TAC) and other disease-modifying antirheumatic drugs (DMARDs). One hundred fifteen rheumatoid arthritis (RA) patients treated with tacrolimus were enrolled in this retrospective analysis. We collected clinical information, including patient background, treatment efficacy (evaluated using the DAS score), and adverse events observed. Multiple logistic regression analysis was conducted to analyze factors contributing to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
3
3
Order By: Relevance
“…Thus, the discrepancy of TAC survival between both studies may be related to the difference in ethnicity among the study subjects, practice guidelines or the incidence of AEs leading to TAC withdrawal. Compared with our data, Ogasawara et al [ 28 ]’s study had a shorter follow-up period and did not evaluate the cause specific survival of TAC. Hence, our study provided more comprehensive data on TAC survival in clinical practice.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the discrepancy of TAC survival between both studies may be related to the difference in ethnicity among the study subjects, practice guidelines or the incidence of AEs leading to TAC withdrawal. Compared with our data, Ogasawara et al [ 28 ]’s study had a shorter follow-up period and did not evaluate the cause specific survival of TAC. Hence, our study provided more comprehensive data on TAC survival in clinical practice.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, only one previous study has calculated the survival figures for TAC in patients with RA. Ogasawara et al [ 28 ] reported that the 1 and 2 year survival rates of TAC in 115 Japanese patients with RA were 57.9% and 48.9%, respectively, which were lower than those in our study. The baseline disease activity, considered as a risk factor for TAC discontinuation in our study, was comparable between the Ogasawara et al [ 28 ]’s study and ours.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Recently, the clinical efficacy of TAC in the management of lupus nephritis has been reported. 5 TAC has also been successfully used in the treatment of RA, 6 and administration of TAC at an oral dose of 3 mg/day was approved for the treatment of lupus nephritis and RA in Japan. On the other hand, reports regarding the use of TAC for SLE patients without renal involvement are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, MTX is contraindicated for patients with kidney function impairment and pregnant women, and may cause clinically significant adverse reactions, including myelosuppression and interstitial pneumonia. These patients may be treated with TAC alone, or salazosulfapyridine, leflunomide, or other DMARDs with or without TAC [5]. The biologic drugs: infliximab (IFX), etanercept (ETN) and tocilizumab (TCZ) have also exhibited good efficacy and safety when administered in combination with TAC [6][7][8].…”
mentioning
confidence: 98%